B-Mode Ultrasound, a Reliable Tool for Monitoring Experimental Intracerebral Hemorrhage - Gómez-de Frutos, Mari Carmen; García-Suárez, Iván; Laso-García, Fernando; Diekhorst, Luke; Otero-Ortega, Laura; Alonso de Leciñana, María; Fuentes, Blanca; Gutiérrez-Fernández, María; Díez-Tejedor, Exuperio; Ruíz-Ares, Gerardo (Frontiers in neurology, 2021)
Background: Magnetic resonance imaging (MRI) is currently used for the study of intracerebral hemorrhage (ICH) in animal models. However, ultrasound is an inexpensive, non-invasive and rapid technique that could facilitate the diagnosis and follow-up of ICH. This study aimed to evaluate the feasibility and reliability of B-mode ultrasound as an alternative tool for in vivo monitoring of ICH volume and brain structure displacement in an animal model. Methods: A total of 31 male and female Sprague-Dawley rats were subjected to an ICH model using collagenase-IV in the striatum following stereotaxic references. The animals were randomly allocated into 3 groups: healthy ( n = 10), sham ( n = 10) and ICH ( n = 11). B-mode ultrasound studies with a 13-MHz probe were performed pre-ICH and at 5 h, 48 h, 4 d and 1 mo post-ICH for the assessment of ICH volume and displacement of brain structures, considering the distance between the subarachnoid cisterns and the dura mater. The same variables were studied by MRI at 48 h and 1 mo post-ICH. Results: Both imaging techniques showed excellent correlation in measuring ICH volume at 48 h ( r = 0.905) and good at 1 mo ( r = 0.656). An excellent correlation was also observed in the measured distance between the subarachnoid cisterns and the dura mater at 1 mo between B-mode ultrasound and MRI, on both the ipsilateral ( r = 0.870) and contralateral ( r = 0.906) sides of the lesion. Conclusion: B-mode ultrasound imaging appears to be a reliable tool for in vivo assessment of ICH volume and displacement of brain structures in animal models.